Complex hemimaxillary rehabilitation with a prefabricated fibula flap and cast-based vacuum-formed surgical template - Nkenke, Emeka; Eitner, Stephan (Journal of Prosthetic Dentistry, 2014)
This report describes a complex, surgical, and prosthodontic hemimaxillary rehabilitation with a prefabricated vascularized free fibula graft. The treatment was based on 3-dimensional skull and fibula models but avoided software-based virtual planning of the reconstructive procedure or the implant positions. Cast-based surgical guides were used for implant placement during prefabrication of the fibula graft and for the positioning of the prefabricated graft in the maxilla during the reconstructive procedure. This procedure allowed the definitive prosthesis to be attached to the implants of the reconstructed maxilla during the inpatient period.
EVALuna2:24363